A produç\~ao agropecuária em Mato Grosso: Produtividade, arrecadaç\~ao fiscal e infraestrutura - José Garcia Gasques; José Eustáquio Ribeiro Vieira Filho; Eliana Teles Bastos; Mirian Rumenos Piedade Bacchi; Constanza Valdes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study aims to analyze the importance of Mato Grosso state in Brazilian agriculture, in terms of its contribution to growth and innovation. Additionally, the role of some municipalities in tax collection was presented, as well as the impact of the EF-170 railway project, better known as "Ferrogr\~ao", on regional productive dynamics. Based on the Agricultural Census, Mato Grosso was one of the states where total factor productivity (TFP) rapidly grew. It is surprising that this productivity index achieved one of the fastest growing worldwide, when compared to a list of more than one hundred countries analyzed by the United States Department of Agriculture (USDA). Internally, in relation to other states, growth comparisons show that Mato Grosso grew at very high rates. In addition to highlighting regional relevance in the context of growth indicators, municipal agricultural hubs boost tax revenue. Furthermore, investments in infrastructure in this region can improve productive growth with better sustainability.
Keywords: O1; O3; O4; 330; productivity; agriculture; growth; infrastructure; sustainability